The importance of an early onset of migraine preventive disease control: A roundtable discussion - Christopher Gottschalk; Anirban Basu; Andrew Blumenfeld; Bradley Torphy; Michael J Marmura; Jelena M Pavlovic; Paula K Dumas; Nim Lalvani; Dawn C Buse (SAGE Publishing, 2022)
Background: Newly approved migraine preventive therapies have allowed for rapid control of migraine activity, offering potential to minimize the burden of migraine. This report summarizes a roundtable discussion convened to analyze evidence for early onset of prevention, ascertain its clinical relevance, and provide guidance for healthcare professionals in crafting goals and treatment expectations for patients with migraine initiating preventive therapy. Methods: A virtual roundtable meeting of migraine clinicians, researchers, and patient advocates convened in October 2020. Participants reviewed and discussed data summarizing patient and healthcare professional perceptions of migraine prevention and evidence from the peer-reviewed and gray literature to develop corresponding recommendations. Summary: Evidence from clinical studies of anti-calcitonin gene-related peptide monoclonal antibodies (erenumab, fremanezumab, galcanezumab, and eptinezumab) and the chemodenervation agent onabotulinumtoxinA indicate that patients may experience reduction of migraine activity within 7 days of drug administration and early attainment of disease control is associated with improvements in clinically important outcomes. The roundtable of experts proposes that early onset be defined as demonstration of preventive benefits within 1 week of treatment initiation. We recommend focusing discussion with patients around "disease control" and potential benefits of early onset of prevention, so patients can set realistic preventive therapy goals and expectations.